2021
DOI: 10.3389/fcell.2021.718974
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value and Immune Landscapes of a m6A/m5C/m1A-Related LncRNAs Signature in Head and Neck Squamous Cell Carcinoma

Abstract: Background: N6-methyladenosine (m6A), 5-methylcytosine (m5C) and N1-methyladenosine (m1A) are the main RNA methylation modifications involved in the progression of cancer. However, it is still unclear whether m6A/m5C/m1A-related long non-coding RNAs (lncRNAs) affect the prognosis of head and neck squamous cell carcinoma (HNSCC).Methods: We summarized 52 m6A/m5C/m1A-related genes, downloaded 44 normal samples and 501 HNSCC tumor samples with RNA-seq data and clinical information from The Cancer Genome Atlas (TC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 88 publications
0
45
1
Order By: Relevance
“…Modification of m 6 A, m 5 C, m 1 A, and m 7 G are the common type of modification in RNA and plays critical roles in cancer development ( Teng et al, 2021 ; Xu F. et al, 2021 ; Xu R. et al, 2021 ). And RNA methylation highly interconnected with hypoxia, immune response and EMT( Lin et al, 2019 ; Chao et al, 2020 ; Wang E. et al, 2021 ). In previous study, researcher identified hypoxia can induced the sumolytion of m 6 A enzyme( Hou et al, 2021 ), hypoxia-inducible factor-1 alpha (HIF-1α) can drive m 5 C modification to promote tumorigenesis( Wang J.…”
Section: Discussionmentioning
confidence: 99%
“…Modification of m 6 A, m 5 C, m 1 A, and m 7 G are the common type of modification in RNA and plays critical roles in cancer development ( Teng et al, 2021 ; Xu F. et al, 2021 ; Xu R. et al, 2021 ). And RNA methylation highly interconnected with hypoxia, immune response and EMT( Lin et al, 2019 ; Chao et al, 2020 ; Wang E. et al, 2021 ). In previous study, researcher identified hypoxia can induced the sumolytion of m 6 A enzyme( Hou et al, 2021 ), hypoxia-inducible factor-1 alpha (HIF-1α) can drive m 5 C modification to promote tumorigenesis( Wang J.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al constructed an m5C-associated lncRNA prognostic signature that accurately predicted breast cancer patient’s prognosis and immune microenvironment characteristics ( Huang et al, 2021 ). A recent study has identified the critical role of m6A/m5C/m1A-related lncRNA-based prognostic signature in predicting molecular subtypes and prognosis of head and neck tumors ( Wang et al, 2021a ). However, to the best of our knowledge, no prognostic signature based on m6A/m1A/m5C/m7G-related lncRNAs has been found to be accurate and applicable to CC patients.…”
Section: Discussionmentioning
confidence: 99%
“…In eukaryotic messenger RNA (mRNA) regulation, N 6methyladenosine (m6A), N 1 -methyladenosine (m1A), and 5methylcytosine (m5C) modifications exist. Several studies have confirmed that m6A, m1A, and m5C regulated genes play important roles in m6A, m1A, and m5C modifications (7)(8)(9)(10)(11). Recent research has found that m6A, m1A, and m5C regulated gene expression levels are associated with tumor progression (11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 91%
“…Currently, the roles of m6A, m1A, and m5C regulated genes in HCC progression are not yet fully understood. Therefore, in this study, data from The Cancer Genome Atlas (TCGA) database were used to elucidate the biological functions and network involved in m6A/m1A/m5C regulated genes ( 8 ), and the roles of m6A/m1A/m5C regulated genes in the prognosis of HCC patients were identified. The risk model and nomogram of m6A/m1A/m5C regulated genes were constructed to determine the prognosis of HCC patients.…”
Section: Introductionmentioning
confidence: 99%